Picture a professor : interrupting biases about faculty and increasing student learning - Neuhaus, Jessamyn (Teaching and learning in higher education (West Virginia University Press), 2022)
"A collection of evidence-based insights and intersectional teaching strategies to inspire transformative student learning and interrupt stereotypes about what a professor looks like. Picture a Professor is a collection of evidence-based insights and intersectional teaching strategies crafted by and for college instructors. It aims to inspire transformative student learning while challenging stereotypes about what a professor looks like. Representing a variety of scholarly disciplines, the volume's contributing authors offer practical advice for effectively navigating student preconceptions about embodied identity and academic expertise. Each contributor recognizes the pervasiveness of racialized, gendered, and other biases about professors and recommends specific ways to respond to and interrupt such preconceptions-helping students, teachers, and others reenvision what we think of when we picture a professor. Educators at every stage of their career will find affirming acknowledgment of the ways systemic inequities affect college teaching conditions, as well as actionable advice about facilitating student learning with innovative course design, classroom activities, assessment techniques, and more"--